2013
DOI: 10.3390/md11010233
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Applications of Sulphated Polysaccharides from Marine Microalgae

Abstract: Marine microalgae have been used for a long time as food for humans, such as Arthrospira (formerly, Spirulina), and for animals in aquaculture. The biomass of these microalgae and the compounds they produce have been shown to possess several biological applications with numerous health benefits. The present review puts up-to-date the research on the biological activities and applications of polysaccharides, active biocompounds synthesized by marine unicellular algae, which are, most of the times, released into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
217
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(232 citation statements)
references
References 89 publications
2
217
0
4
Order By: Relevance
“…In the meantime, the ever-increasing demand for antithrombotic therapy calls for alternative sources of anticoagulant and antithrombotic compounds [8]. It has been shown that sulfated polysaccharides with anticoagulant activity are most abundant in marine invertebrates and marine algae [9,10]. Hence, abalone gonads could eventually become a valuable source of polysaccharides with anticoagulant properties.…”
Section: Preparation and Characterization Of Abalone Gonad Polysacchamentioning
confidence: 99%
See 2 more Smart Citations
“…In the meantime, the ever-increasing demand for antithrombotic therapy calls for alternative sources of anticoagulant and antithrombotic compounds [8]. It has been shown that sulfated polysaccharides with anticoagulant activity are most abundant in marine invertebrates and marine algae [9,10]. Hence, abalone gonads could eventually become a valuable source of polysaccharides with anticoagulant properties.…”
Section: Preparation and Characterization Of Abalone Gonad Polysacchamentioning
confidence: 99%
“…This result suggested that both the molecular weight and degree of sulfation have essential influences on the anticoagulant activity of polysaccharides. Furthermore, the anticoagulant properties of the polysaccharides do not depend only on the percentage of sulphate residues, but rather, mostly on the distribution or position of sulphate groups and probably on the configuration of the polymer chains [9].…”
Section: Anticoagulant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of microalgae species, depending on the culture conditions, the synthesized polysaccharides are heteropolymers composed mainly of a combination of sugars such as glucose, xylose and galactose, among others. [132]. For this reason, there is a broad spectrum of bioactive compounds with different molecular weights, ionic charges and properties that can have a high value application in various industries such as mechanical engineering, food or biomedicine.…”
Section: Functional Polysaccharidesmentioning
confidence: 99%
“…accumulate EPA, but their commercial production is still not very consolidated. The global market for PUFAs, especially DHA and EPA, is growing exponentially [132]. The consumption of DHA / EPA functional products, especially in regions such as North America, Europe and Asia, represented USD 25.4 billion in 2011 and USD 34.7 billion in 2016 [133].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%